Gas Humidification Impact on the Properties and Performance of Perovskite-Type Functional Materials in Proton-Conducting Solid Oxide Cells - Wang, Wei; Medvedev, D.; Shao, Zongping (Wiley, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Fuel cells and electrolysis cells as important types of energy conversion devices can be divided into groups based on the electrolyte material. However, solid oxide cells (SOCs) based on conventional oxygen-ion conductors are limited by several issues, such as high operating temperature, the difficulty of hydrogen purification from water, and inferior stability. To avoid these problems, proton-conducting oxides are proposed as electrolytes for SOCs in electrolysis and fuel cell modes. Since water vapor partial pressure (pH2O) is one of the main parameters determining the proton concentration in proton-conducting oxides (characteristics of which can be either improved or deteriorated), the pH2O control is extremely important for the optimization of the devices' performance and stability. This review provides an overview of the research progresses made for proton-conducting SOCs, especially for the impact of gas humidification on the operability and performance. Fundamental understanding of the main processes in proton-conducting SOCs and design principles for the key components are summarized and discussed. The trends, challenges, and future directions that exist in this dynamic field are also pointed out. This review will inspire interest from various disciplines and provide some useful guidelines for future development of proton-conductor-based energy storage and conversion systems.